OTU-009 Modelling caseload standards for IBD specialist nurses in the UK. (8th June 2018) - Mason, Isobel; Leary, Alison
Abstract : Introduction: The national standards for IBD care defined the numbers of nurse specialists required as 1.5 FTE per 2 50 000 population. The aim was to publish a new, robust, validated national standard and caseload. Methods: A concensus workshop of 15 IBD nurse specialists from across the UK met to check assumptions regarding workload and activity of this group. A 24-item questionnaire, exploring demographic data, caseload, workload and experience was developed. This was was distributed through the RCN IBD Nursing Network. Data was modelled using descriptive statistics and pattern recognition. Results: 164 responses were received (55% response rate). 76% were from England. Responses were received from all four countries of the U.K. Most respondents covered a single (60%) or two (25%) hospital sites. 38% of respondents had less than 3 years experience working with IBD patients. 62% having four years plus experience. 32% had over ten years' experience. 90% of the responding CNS were working solely in IBD. 82% reported spending 80% to 100% of their time on IBD. 51% worked with adult and transition patients. 72% of respondents worked full time. 84% of respondents regularly carried out unpaid overtime. The amount of unpaid overtime carried out equalled 17.6 FTE per week. Most common title was 'Clinical Nurse Specialist'. Grade 7 most common grade for respondents (65%). 61% received either no admin support or support for clinic letters only. The number of unfilled posts was estimated to be equivalent to 24.5 FTE. No respondents reported frozen posts. 43% of respondents had a prescribing qualification. 82% reported participation in CPD/education within the last 12 months. 63% of respondents had a higher caseload than the recommended level. Caseloads as high as 2000 patients plus were reported. Respondents generally had a positive experience of working in an MDT. Conclusions: This study recommends a caseload of 2.5 Full Time Equivalent (FTE) IBD specialist nurse per 2 50 000 population (a static caseload of 500 per FTE). The original recommended caseload for IBD specialist nurses is 666 patients (or 1.5 FTE per 2 50 000 population) per FTE nurse. This does not allow for proactive management, advancing practice, cover arrangements and is not optimal for care. There is a shortfall in the UK. 63% have much higher caseloads than the original recommended standard. Compared to other specialities IBD specialist nurses have been working in specialist practice for less time (for example 52% had less than 7 years' experience vs 25% of prostate cancer specialist nurses). Considerable amount of unpaid overtime (4.13 hours per week each on average, equal to 17.6 FTE per week in total in this group). Worsened where administrative support is limited. 43% of respondents have a prescribing qualification only 14% have a Masters in advanced practice. To achieve a greater number of advanced practice nurses, this is an issue which needs to be addressed in light of the reduction in funding for continuing professional development nationally. IBD specialist nurses generally have a positive experience of Multidisciplinary Team working (MDT) and feel able to fully contribute and advocate for patients within the MDT The role of the IBD specialist nurse is a complex case managing role involving interacting with many other specialities to deliver care for the patient population over their entire treatment pathway from pre diagnosis to continuing care.